PEMBAHARUAN CRIMINAL POLICY TENTANG SISTEM PERTANGGUNGJAWABAN PIDANA KORPORASI (Upaya Strategis dalam Penaggulangan Kejahatan Korporasi) - Zulkarnain Zulkarnain; Zahir Rusyad (Widya Yuridika, 2018)
Corporation crime is as extra ordinary crime we should fight against seriously. Great efforts must be made in order to remove this crime. Such effortst, however, are not in a direct proportion with the criminal policy serving as a base in its law enforcement. The criminal codes serving as the main legal law turn out just considering natural people as a subject of criminal law that may be criminaly assumed, instead of recognizing corporations as the subject of the criminal law, although in some corporation arrangements out of the criminal codes, there are some schemas that recognize corporations as a subject of law. Such arrangements, however are still doubtfully made, since the recognition of corporations as a subject of law in the law still denies the responsibility and comdemnation of corporation in the Indonesian criminal law still refer to a paradigm that position a person as a doer of crimes. As a result, although it is clear that the actor of crimes is a corporation, it is the natural person who should be responsible for the crime.  Kata Kunci: korporasi, pertanggungjawaban pidana.